Predictive Validity of the CRAFFT for Substance Use Disorder - Shenoi, Rohit P. (Pediatrics, 2019)
BACKGROUND: The utility of CRAFFT (Car, Relax, Alone, Forget, Friends, Trouble) in identifying current and future problematic substance use and substance use disorders (SUDs) in pediatric emergency department (PED) patients is unknown. We conducted a secondary analysis of a study in 16 PEDs to determine the concurrent and predictive validity of CRAFFT with respect to SUD. METHODS: At baseline, 4753 participants aged 12 to 17 years completed an assessment battery (CRAFFT and other measures of alcohol, drug use, and risk behaviors). A subsample was readministered the battery at 1-, 2-, and 3-year follow-up to investigate future SUDs. RESULTS: Of 2175 participants assigned to follow-up, 1493 (68.6%) completed 1-year, 1451 (66.7%) completed 2-year, and 1265 (58.1%) completed the 3-year follow-up. A baseline CRAFFT value of ≥2 was significantly associated with problematic substance use or mild or moderate to severe SUD diagnosis on the Diagnostic Interview Schedule for Children at baseline (P < .001). The results persisted after 1, 2, and 3 years (P < .001). The best combined sensitivity and specificity was achieved with a baseline CRAFFT value of ≥1 as a cutoff for predicting problematic substance use and a Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition diagnosis of mild SUD at 1, 2, and 3 years. The baseline CRAFFT score that best predicted a moderate to severe SUD at 1 year was ≥2; but at 2 and 3 years, the cutoff score was ≥1. CONCLUSIONS: CRAFFT has good concurrent validity for problematic substance use and SUD in PED patients and is useful in predicting SUDs at up to 3 years follow-up but with limited sensitivity.